(untitled) (International Journal of Engineering and Computer Science, 2017)
The today’s enterprise systems usually form a system of sub-applications, each being responsible for a particular functionality. Hence, the design and maintenance of such a complex system is not a simple task. In addition, the user requirements can change and the affected parts need to be identified and evolved. Similarly, new components or even whole system may need to be integrated. Companies in order to build and sustain competitive advantage have to rely more and more on their IT systems in virtually every aspect of their business operations. In spite of this and despite their critical operational, tactic and strategic role, many new and old IT systems have either not offered what they were created for, or have failed outright. Many of these failures and inadequacies result from a poorly executed development process. The development processes used employ either inadequate development models or flawed implementation due, in part, to the lack of proper frameworks and effective collaborative mechanisms between the development and integration functions. This puts forward high requirements on information systems and in turn, raises a great challenge to software developers. In order to build and sustain such systems, an integrated framework is needed for building and implementing business applications to automate business processes and support the business functions of the enterprise. The method adopted for the design is the Iterative Design Method. An integrated architecture framework was developed as a tool for efficient implementation of enterprise system as the end objective. Comprehensive system frameworks are necessary to capture the entire complexity of such systems. The architecture framework provides the conceptual foundation that includes Business, Information, information system, infrastructure and governance and security views necessary for building and managing the integral business system and all its components and also provides an integrated description of enterprise information systems in terms of the instantiation of the architecture framework.